New vision of digital teaching competence in times of pandemic - ESTEVE MON, Francesc M.; LLOPIS NEBOT, María Ángeles; ADELL SEGURA, Jordi (Utopía y Praxis Latinoamericana, 2021)
The COVID-19 pandemic has highlighted the existence of different tensions and gaps related to digital teaching competence (DTC) and the pedagogical use of technology. It is a competence that cannot be reduced to the utilitarian nature of technology, but rather implies a new vision of teaching in a digital world. Starting from the different approaches to the concept of DTC, in this article we discuss on the elements that make it up and its controversies, raising different key aspects: pedagogy, critical thinking with technology and social commitment.